Small non-coding RNAs: key regulatory factors and potential therapeutic targets in tumor immunity - Liu, Zihan; Dong, Haotian; Ye, Chengyuan; Yan, Jianing; Miao, Min; Shao, Yongfu (Frontiers in Immunology, 2025)
Tumor immunity has emerged as a focal point for cancer research. Although tumor immunotherapy represents a promising approach to cancer treatment, its effectiveness is often hindered by the heterogeneity of the tumor microenvironment (TME) and immune escape mechanisms. In recent years, small non-coding RNAs (sncRNAs) have attracted increasing attention in tumor immunology due to their essential role in gene regulation. This review systematically examines the multifaceted regulatory functions of sncRNAs in tumor immunity, with a focus on six major subtypes: microRNA, siRNA, piRNA, snoRNA, tsRNA, and snRNA. The molecular mechanisms by which these sncRNAs reshape the TME are discussed, including their roles in modulating immune cell differentiation (e.g., T cell polarization, macrophage phenotype transition), regulating immune checkpoint expression (PD-1/PD-L1, CTLA-4, Tim-3, LAG-3), and influencing tumor antigen presentation. This review also explores the dynamic network through which sncRNAs contribute to tumor immune escape. Furthermore, this study highlights the clinical potential of sncRNAs as liquid biopsy biomarkers and their application prospects in therapeutic strategies, such as targeted silencing of immunosuppressive molecules via nano-delivery systems, combination treatments with radiotherapy and chemotherapy, and Chimeric Antigen Receptor T-cell (CAR-T) therapy. Despite current challenges, including limited delivery efficiency and off-target effects, emerging technologies like AI-assisted sequence design and organ-on-a-chip models present new opportunities for clinical translation. This comprehensive review provides a theoretical foundation and translational insights for elucidating the functional network of sncRNAs in tumor immunology and advancing precise therapeutic interventions.